DESIGNING IMMERSIVE PEDAGOGIES: VIRTUAL REALITY AS A CATALYST FOR STUDENT-CENTRED AND CO-CREATIVE LEARNING IN HERITAGE EDUCATION - Radzuan , Ainul Wahida; Hapiz , Hana Yazmeen; Abdul Latef , Azlin Sharina (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the use of Virtual Reality (VR) in enhancing heritage education by shifting the focus from conventional content delivery to immersive, student-centred learning experiences. While VR has become increasingly popular in education, its integration within heritage studies, particularly in Southeast Asia, remains limited. Guided by Kolb’s Experiential Learning Theory, a seven-week classroom intervention was conducted with 30 undergraduate students enrolled in the Cultural Heritage Conservation course at Universiti Malaysia Kelantan. The study employed a mixed-methods approach that combined survey responses, reflections, and interviews to examine how VR shapes students’ spatial understanding, emotional engagement, and interpretive skills in heritage learning. Findings indicate a strong level of agreement among participants (mean: 4.35–4.43) that VR enhances their ability to visualise spatial arrangements, appreciate cultural significance, and experience deeper emotional connection with heritage sites. Qualitative feedback further confirms VR’s potential to position students as active interpreters rather than passive recipients of information. This study highlights the transformative potential of VR as a pedagogical tool in heritage education, offering a scalable, cost-effective, and inclusive model that bridges theoretical instruction with experiential engagement.